Identifikasi Habitat Alami Maleo Senkawor (Macrocephalon Maleo) Di Kawasan Konservasi Hungayono Taman Nasional Bogani Nani Wartabone - Diko, Ahmad Fauzi C; Yusuf, Daud; Rusiyah, Rusiyah (Universitas Negeri Gorontalo, 2025)
This study aims to identify and describe the natural habitat of the maleo senkawor (Macrocephalon maleo) in the Hungayono area of Bogani Nani Wartabone National Park, and to compile a distribution map. The method used is descriptive qualitative through field observations, interviews, and journal literature. The results show that the maleo habitat is characterized by warm sandy soil due to geothermal activity, protective vegetation, and proximity to rivers. The distribution pattern of the habitat is clustered, indicating a high dependence on certain ecological conditions. The main threats come from natural predators and habitat changes due to natural disasters. These findings emphasize the importance of spatial-based conservation focused on locations with high habitat suitability to ensure the sustainability of the maleo senkawor population.